The Earned Income Tax Credit and Maternal Time Use: More Time Working and Less Time with Kids? - Bastian, Jacob; Lochner, Lance (Journal of Labor Economics, 2022)
Parents spend considerable time and resources investing in their children’s development. Given evidence that the Earned Income Tax Credit (EITC) affects maternal labor supply, we investigate how the maximum available EITC amount affects a broad array of time use activities, focusing on the amount and nature of time spent with children. Using 2003–18 time use data, we find that federal and state EITC expansions increase maternal work time, reducing time devoted to home production, leisure, and time with children. However, almost none of the reduction comes from time devoted to “investment” activities, such as active learning and development activities.